Modeling of Audio System Assembly Line Activities Using Simulation - Zurina, Hanafi (2003)
The manufacturing sector has become an essential sector in Malaysia. This sector needs to be efficient and sound in facing great competition. Reducing costs will ensure that manufacturing companies remain competitive in the market. This study was conducted in a manufacturing company that produces audio systems by using simulation technique. Simulation technique would help the management team in making the right decisions. The objectives of the study are to identify the problems arising in the system and to forecast the throughput based on several scenarios. The aim of these scenarios is to see the system performance. System performance is determined by looking at total output and cycle time. Besides that, the percentage of resource utilization, waiting time and queue time is also taken into consideration. After that, three scenarios were built in order to see the performance of the system after the throughputs are increased. ARENA@ software was used in modeling the system.